Estado forestal del Pinus caribaea Morelet var. hondurensis en El Pinal, Laguna de Perlas, RAAS - Campbell Howard, A.; Machado García, R.; Lopez Larios, J. Asesor; Calero Gonzalez, C.A. Asesor (Managua (Nicaragua), 2001)
Sumarios (Es, En)
Ilus.; 22 ref.
Tesis (Ing Agr)
Keywords: PINUS CARIBAEA; RECURSOS FORESTALES; BOSQUES; VEGETACION; PLANTACION FORESTAL; EL PINAL; LAGUNA DE PERLAS; RAAS